THE DURABILITY OF YELLOW-POPLAR AND AMERICAN BEECH TREATED WITH CHROMATED COPPER ARSENATE. - SLAHOR, JEFFREY J. ; HASSLER, CURT C. ; DAWSON-ANDOH, BENJAMIN
DURABILIDAD OF YELLOW-POPLAR AND AMERICAN BEECH TREATED WITH CHROMATED COPPER ARSEMATE (CCA) WAS EVALUATED IN FIELD PLOTS IN WEST VIRGINIA AND MISSISSIPPI.....